2006
DOI: 10.1128/iai.74.3.1649-1660.2006
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Highly Expressed Genes Are Disease Specific

Abstract: During in vitro broth culture, bacterial gene expression is typically dominated by highly expressed factors involved in protein biosynthesis, maturation, and folding, but it is unclear if this also applies to conditions in natural environments. Here, we used a promoter trap strategy with an unstable green fluorescent protein reporter that can be detected in infected mouse tissues to identify 21 Salmonella enterica promoters with high levels of activity in a mouse enteritis model. We then measured the activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 84 publications
2
69
0
Order By: Relevance
“…4A and Table S1 in the supplemental material). Furthermore, the positive regulation of SPI-1 genes by FNR, the global anaerobic activator, corroborates previous findings showing that oxygen limitation increases the expression of SPI-1 invasion genes (3,39,46) and that an fnr mutant is nonvirulent in the enteritis mice model (69).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…4A and Table S1 in the supplemental material). Furthermore, the positive regulation of SPI-1 genes by FNR, the global anaerobic activator, corroborates previous findings showing that oxygen limitation increases the expression of SPI-1 invasion genes (3,39,46) and that an fnr mutant is nonvirulent in the enteritis mice model (69).…”
Section: Discussionsupporting
confidence: 77%
“…Although several studies have shown that oxygen limitation induces adhesion and invasion in Salmonella (19,40,53,73), it was concluded that "oxrA (fnr) is not involved in the regulation of Salmonella invasiveness" (53). However, in a recent study (69), fnr was shown to be essential for the virulence of serovar Typhimurium SL1344 in the enteritis mice model. Thus, the most likely explanation for the differences between our findings and those reported previously (53,76,87) relates to the strain of Salmonella employed.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of srfJ (STM4426) results in a slight attenuation with respect to the systemic virulence in mice (Ruiz-Albert et al, 2002). Moreover, a yet unknown regulatory gene was shown to be upregulated in the gut using an enteritis mouse model (Rollenhagen & Bumann, 2006). Several gut pathogens carry iol gene homologues (Table 1), although a contribution of myo-inositol degradation to the virulence properties of Clostridium perfringens or Y. enterocolitica has not been demonstrated.…”
Section: Inositolmentioning
confidence: 99%
“…The recently obtained genome sequences of two virulent Chinese S. suis serotype 2 strains (98HAH12 and 05ZYH33) and P1/7, the European reference strain (http://www.sanger.ac.uk/Projects/S_suis/), led to the identification of a large number of potential surface and secreted proteins that might play a role in virulence, including a number of putative carbohydratedegrading enzymes (Baums & Valentin-Weigand, 2009). Genes that encode carbohydrate-degrading enzymes are common in the genomes of other streptococcal pathogens and play a role in nutrient acquisition for growth and colonization on mucosal surfaces (Rollenhagen & Bumann, 2006;Shelburne et al, 2006Shelburne et al, , 2008a. Dietary sources of highly polymerized a-glycans such as starch and glycogen are abundant in the human colon (Levitt et al, 1987) and oropharynx (Mormann & Muhlemann, 1981;Shelburne et al, 2005 Shelburne et al, , 2007Virtaneva et al, 2005), as well as the epithelium of the vagina and lung (Gourlay et al, 2009;Gregoire et al, 1971; Santi et al, 2008;van Bueren et al, 2007).…”
mentioning
confidence: 99%